2018
DOI: 10.1038/s41467-018-06213-1
|View full text |Cite
|
Sign up to set email alerts
|

Human hippocampal replay during rest prioritizes weakly learned information and predicts memory performance

Abstract: The hippocampus replays experiences during quiet rest periods, and this replay benefits subsequent memory. A critical open question is how memories are prioritized for this replay. We used functional magnetic resonance imaging (fMRI) pattern analysis to track item-level replay in the hippocampus during an awake rest period after participants studied 15 objects and completed a memory test. Objects that were remembered less well were replayed more during the subsequent rest period, suggesting a prioritization pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

31
225
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 230 publications
(259 citation statements)
references
References 55 publications
31
225
3
Order By: Relevance
“…Even without such external modulator, it seems that the brain has its own selection mechanism. Recent study showed that the brain prioritizes weakly learned information and predicts later performance (Schapiro, McDevitt, Rogers, Mednick, & Norman, 2018). Together with this line of studies, the current study adds the evidence that the reactivation favors novel and salient information.…”
Section: Discussionsupporting
confidence: 77%
“…Even without such external modulator, it seems that the brain has its own selection mechanism. Recent study showed that the brain prioritizes weakly learned information and predicts later performance (Schapiro, McDevitt, Rogers, Mednick, & Norman, 2018). Together with this line of studies, the current study adds the evidence that the reactivation favors novel and salient information.…”
Section: Discussionsupporting
confidence: 77%
“…Sequential learning-related spiking activity was shown to "replay" during sleep, and this phenomenon has since been connected to the off-line consolidation process 6 . In Humans, recent studies using multivariate pattern classification analysis in fMRI have also shown evidence for reactivation of cortical and hippocampal memory-related patterns during sleep and awake rest 7,8,9,10 .An important milestone in the study of sleep-related reactivation has been the development of targeted memory reactivation (TMR), a paradigm designed to reactivate specific memories by unobtrusively presenting learning-related cues during sleep 11 . TMR has been shown to improve various forms of learning, including spatial 12, 13 , skill 14, 15 and vocabulary 16 learning.…”
mentioning
confidence: 99%
“…Sequential learning-related spiking activity was shown to "replay" during sleep, and this phenomenon has since been connected to the off-line consolidation process 6 . In Humans, recent studies using multivariate pattern classification analysis in fMRI have also shown evidence for reactivation of cortical and hippocampal memory-related patterns during sleep and awake rest 7,8,9,10 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research in humans has found that hippocampal activity during reward learning co-varies with the activation of associated items in the visual cortex 12 and that hippocampal activity patterns represent retrieved information about currently cued target locations 50 . Recent papers have reported reactivation of hippocampal activity patterns during rest periods following learning 51,52 and that hippocampal activity co-varies with the reactivation of visual stimuli 53 . Interestingly, in recent work using MEG, an imaging method with much faster temporal resolution, Kurth-Nelson et al 54 reported that fast sequences of activity reflected potential trajectories in a non-spatial environment.…”
Section: Discussionmentioning
confidence: 99%